LANGUAGE SKILLS OF DEAF CHILDREN AT JOMBANG STATE EXCEPTIONAL SCHOOL - Heny Sulistyowati (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
Deaf children show hearing difficulties from mild to severe categories, classified into hearing loss and deafness. Deaf people are people who have lost the ability to hear so that it hinders the process of language information through hearing, either using or not using hearing aids where the hearing limit they have is sufficient to allow the success of the process of language information through hearing. Deaf children need learning media in the form of teaching aids to enrich their language vocabulary. The props include miniature animals, human miniatures, relevant pictures, illustrated library books, and children's play tools. The method used in this study is a qualitative descriptive method through an observation. Observations are carried out in stages over several days starting from making an approach to making direct observations of objects. The results of observations made to Agus are guided by 4 language skills. Based on the four language skills, the object is able to master in writing skills. Listening skills are not mastered because the object has problems in hearing but can be overcome by the lip motion method. Object reading skills can understand but difficult to convey as well as speaking skills.